Bitter Taste Receptors (TAS2Rs) in Human Lung Macrophages: Receptor Expression and Inhibitory Effects of TAS2R Agonists - Grassin-Delyle, Stanislas; Salvator, Hélène; Mantov, Nikola; Abrial, Charlotte; Brollo, Marion; Faisy, Christophe; Naline, Emmanuel; Couderc, Louis-Jean; Devillier, Philippe (Frontiers in Physiology, 2019)
Background: Bitter-taste receptors (TAS2Rs) are involved in airway relaxation but are also expressed in human blood leukocytes. We studied TAS2R expression and the effects of TAS2R agonists on the lipopolysaccharide (LPS)-induced cytokine release in human lung macrophages (LMs). Methods: Lung macrophages were isolated from patients undergoing surgery for carcinoma. We used RT-qPCR to measure transcripts of 16 TAS2Rs (TAS2Rs 3/4/5/7/8/9/10/14/19/20/31/38/39/43/45 and 46) in unstimulated and LPS-stimulated (10 ng.mL-1) LMs. The macrophages were also incubated with TAS2R agonists for 24 h. Supernatant levels of the cytokines TNF-α, CCL3, CXCL8 and IL-10 were measured using ELISAs. Results: The transcripts of all 16 TAS2Rs were detected in macrophages. The addition of LPS led to an increase in the expression of most TAS2Rs, which was significant for TAS2R7 and 38. Although the promiscuous TAS2R agonists, quinine and denatonium, inhibited the LPS-induced release of TNF-α, CCL3 and CXCL8, diphenidol was inactive. Partially selective agonists (dapsone, colchicine, strychnine, and chloroquine) and selective agonists (erythromycin (TAS2R10), phenanthroline (TAS2R5), ofloxacin (TAS2R9), and carisoprodol (TAS2R14)) also suppressed the LPS-induced cytokine release. In contrast, two other agonists (sodium cromoglycate (TAS2R20) and saccharin (TAS2R31 and 43)) were inactive. TAS2R agonists suppressed IL-10 production - suggesting that this anti-inflammatory cytokine is not involved in the inhibition of cytokine production. Conclusions: Human LMs expressed TAS2Rs. Experiments with TAS2R agonists’ suggested the involvement of TAS2Rs 3, 4, 5, 9, 10, 14, 30, 39 and 40 in the inhibition of cytokine production. TAS2Rs may constitute new drug targets in inflammatory obstructive lung disease.